Penetrasi Nilai-Nilai Kepemimpinan Bigman dalam Pemerintahan Kampung di Kabupaten Manokwari Selatan - Indouw, Yulianus; Silo, Akbar; Saa, Septinus; Muhdiarta, Untung (JURNAL EKOLOGI BIROKRASI, 2023)
The overall objective of the research is to identify the penetration of bigman leadership values in village governance in Oransbari District, South Manokwari Regency. This research uses an exploratory paradigm, a descriptive approach with qualitative research (in-depth interviews). The data collection methods used were observation, interviews and documentation. Data analysis follows the procedures of data collection, data presentation and drawing conclusions. The results of these findings show that the penetration of big man leadership values in village governance in Masabui one Masabui two Watariri villages is still controlled by traditional values, especially the value of power and ownership of customary rights and rights as a tribal chief, which are used in governance starting from the leader. The village structure prioritises the values of responsibility and transparency, even though it is controlled by a patrilineal family. The penetration of bigman leadership values in village governance in Oransbari District, South Manokwari Regency, has had a very strong influence. This influence is due to the power system of the tribal chief as the holder of customary rights, which has become a customary provision that all organisations entering the village must be headed by the holder of customary rights, who is also the local tribal chief, including bodies in the organisational structure, because it has become customary. As a legacy from generation to generation, all the trust of the community will be directed towards him. In addition, as the head of the village, the tribal chief plays an important role and is fully responsible for all government programmes that come to the village. He is also responsible for solving all problems related to violations and disputes in the village.